Participation of students in the project Valorbio: A case study to accelerate the implementation of sustainability principles in the curriculum - Mateus, D. M. R. (2021)
Purpose – The present work describes the case of the Valorbio research project, in which students of different high-level programs were involved in the experimental work and in the dissemination of results in collaboration with the research team. Design/methodology/approach – The inclusion in higher education curricula of content related to the sustainable development should be a preferred mechanism for the dissemination of good practices of sustainability. Another equally important way to achieve this is to involve students in research projects that seek solutions to the societal challenges related to sustainable growth. The Valorbio project aims to meet the needs for treating and reusing wastewater and solid waste. Its main goal was the development of modular systems for wastewater treatment based on constructed wetlands,exploring the possibility of the treatment systems being composed of solid waste and by-products from significant industrial sectors. Findings – The students’ contributionto the research workwas relevant, and simultaneously allowedthem to acquire skills on sustainable development. Additionally, the students contributed to the dissemination of the results. The Valorbio project can thus be considered a successful application of the concept of project-based learning,as a way to include sustainability issues content in the higher education curricula. Originality/value – The applied experimental work had an original approach regarding the equipment design, the waste materials valuation, as well as the integration of waste treatment processes in the circular economy paradigm.This paper is the first reported project-based learning experience involving students of short-cycle technical-professional programs in partnership with first and second-level students and a research team.